English Teachers’ Perspectives on Challenges, Suggestions, and Materials of Online Teaching amidst the Global Pandemic - Novrika Nartiningrum; Arif Nugroho (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTMaintaining undisrupted learning during this pandemic becomes a challenge for teachers all over the world. In Indonesia, the practices of open online learning are not yet to be implemented. Online learning in Secondary school Year 7-9 level goes as far as internet-assisted learning or blended learning. Thus, previous research has not examined teachers' perspectives on full online learning as implemented during the Covid-19 pandemic. Considering this situation, EFL Secondary school Year 7-9 teachers’ perspectives, as one of the essential aspects of online learning, lack investigation. Therefore, the present study offers 20 EFL Secondary school Year 7-9 teachers’ insights regarding challenges, suggestions, and teaching materials needed during the Covid-19 outbreak. Drawing on qualitative data collected by means of self-written reflections and semi-structured interviews, the findings informed that poor internet signal disrupts the teaching process. Thus, the teachers suggest that maintaining a stable internet connection should become a priority. Then, easy access to online applications and websites is deemed necessary by teachers as material sources for online teaching. The results of this study contribute to the literature of English language teaching in response to the present-day phenomenon about online learning, particularly in Secondary school Year 7-9 level. ABSTRAKMempertahankan pembelajaran tanpa gangguan selama pandemic ini menjadi tantangan bagi para guru di seluruh dunia. Di Indonesia, praktik pembelajaran online terbuka masih belum diterapkan. Pembelajaran online di Sekolah Menengah tingkat 7-9 masih sejauh pembelajaran dengan bantuan internet atau pembelajaran campuran. Dengan demikian, penelitian sebelumnya belum mengkaji perspektif guru tentang full online learning sepertin yang diterapkan selama pandemi Covid-19. Mempertimbangkan situasi ini, perspektif guru EFL Sekolah Menengah Kelas 7-9, sebagai salah satu aspek penting dari pembelajaran online, belum diselidiki. Oleh karena itu, penelitian ini menawarkan perspektif dari 20 guru 20 EFL Sekolah Menengah Kelas 7-9 tentang tantangan, saran dan bahan pengajaran yang dibutuhkan selama wabah Covid-19. Berdasarkan data kualitatif yang dikumpulkan melalui refleksi yang ditulis sendiri dan wawancara semi-terstruktur interviews, temuan menginformasikan bahwa sinyal internet yang buruk mengganggu proses pengajaran. Oleh karena itu, para guru menyarankan bahwa menjaga koneksi internet yang stabil harus menjadi prioritas. Kemudian, aplikasi dan website online yang mudah diakses dianggap dibutuhkan oleh guru sebagai sumber materi pembelajaran online. Hasil penelitian ini berkontribusi pada literatur pengajaran Bahasa Inggris dalam menanggapi fenomena pembelajaran online saat ini, khususnya di tingkat Sekolah Menengah Kelas 7-9.